2015
DOI: 10.1186/s12936-015-0645-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient adherence to prescribed artemisinin-based combination therapy in Garissa County, Kenya, after three years of health care in a conflict setting

Abstract: BackgroundCurrent day malaria cases and deaths are indicative of a lack of access to both methods of prevention, diagnosis, and treatment; an important determinant of treatment efficacy is adherence. This study is a follow up to the baseline study of adherence to artemether-lumefantrine (AL) carried out in Garissa District in 2010. The study presented evaluates any changes in adherence levels which may have occurred in the area during this period and after nearly three years of sustained use of ACT across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
3
8
5
Order By: Relevance
“…19 The study finding is also in agreement with the findings of Amponsah et al, Gore-Langton et al, Yeung and White, where they reported low adherence level to antimalarial medications. [29][30][31] The current study finding disagrees with Aung et al, where (85.7%) of respondents in Rakhine State, Myanmar were classified as probably adherent, and 23 (14.3%) as non-adherent group. 2 Also, the study finding is not in accordance with Fogg et al where they reported high adherence to the combination of Artemether and Lumefantrine in Uganda in which 90% of the children were documented as being probably adherent, 7.1% being definitely non-adherent.…”
Section: Discussioncontrasting
confidence: 99%
“…19 The study finding is also in agreement with the findings of Amponsah et al, Gore-Langton et al, Yeung and White, where they reported low adherence level to antimalarial medications. [29][30][31] The current study finding disagrees with Aung et al, where (85.7%) of respondents in Rakhine State, Myanmar were classified as probably adherent, and 23 (14.3%) as non-adherent group. 2 Also, the study finding is not in accordance with Fogg et al where they reported high adherence to the combination of Artemether and Lumefantrine in Uganda in which 90% of the children were documented as being probably adherent, 7.1% being definitely non-adherent.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that there was no signi cant relationship between patients demographics and their compliance with antimalarial drugs treatment and that was consistent with the ndings of a study carried out in Uganda [28]. Stopping treatment after symptoms improvement [29] and upon the development of ADRs [30] was shown in some studies and it was found that drug knowledge and previous experience of drug use were signi cant predictors of adherence to treatment [31]. Patient education on noncompliance to treatment and its drawbacks not only for the patients but also for the whole country as a risk of drug resistance is very crucial.…”
Section: Discussionsupporting
confidence: 83%
“…When meta-analysis was restricted to the eighteen studies (and two sub-studies) [12, 22, 24, 25, 2831, 3440, 42, 43, 45] that administered AL, the REM pooled prevalence of adherence (95% CI) was 70.52% (60.82%–80.22%). No publication was detected (Begg's test P value = 0.056 and Egger's test P value = 0.018).…”
Section: Resultsmentioning
confidence: 99%